Factors affecting the demand for reinsurance An applied study on private insurance companies operating in Syria during period 2010-2020 - حسن , رفاه; حنان ضاهر , (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This study aimed to investigate the factors affecting the demand for reinsurance of 12 private insurance companies operating in Syria during the period 2010-2020, through annual data obtained from the financial reports of the companies under study. To achieve the purpose of the study, the static panel models were relied upon after ensuring the stability of the data at the level. The study concluded that there is a positive effect for each of the ratio of technical reserves to the net premiums and the life insurance share of the total premiums, meaning that these ratios rise in the studied insurance companies leads to an increase in the demand for reinsurance; On the other hand, the study found a negative impact on the retention rate, company size, and company profitability, represented by the return on equity. While the study did not find a significant effect of financial leverage, concentration ratio and underwriting risk.